PERANCANGAN GEDUNG PUSAT WISATA EDUKASI DANAU TONDANO DI MINAHASA - Sarendaren, Yustri; Warouw, Felly Ferol; Katuuk, Antoniette L. Grace (Jurnal Ilmiah Desain Sains Arsitektur (DeSciArs), 2025)
Lake Tondano located in Minahasa North Sulawesi province is a lake that has significant tourism and ecological potential but has yet to be properly explored or utilized Issues such as water pollution sedimentation and a lack of educational support facilities pose major challenges The Tondano Lake Educational Tourism Center utilizing a Biophilic Architecture approach aims to combine tourism and education functions while also serving as a spearhead in raising public awareness about the preservation of the Tondano lake ecosystem The design results will include plans elevations sections and other details that describe the outcomes of the existing synthesis Natural lighting settings and environmentally friendly materials This Education Tourism Center is expected to become an educational and sustainable tourist destination while also encouraging local economic growth.